When the impossible happens : confessions of a reluctant psychic - Licauco, Jaime T. (Pasig City, Philippines : Published and exclusively distributed by Anvil Pub., 1999)
1. Parapsgchology 2. Clair--voyance 3. Subcons ciousness
Faculty